Analisis kesulitan peserta didik dalam menyelesaikan soal numerasi pecahan pada Asesmen Kompetensi Minimum di sekolah dasar - Windi Mugi Lestari; Joko Daryanto; Hadiyah Hadiyah (Didaktika Dwija Indria, 2023)
The purpose of this study was to describe the implementation of the Minimum Competency Assessment, describe the difficulties of students in solving fraction numeracy problems on the Minimum Competency Assessment, and describe the efforts of Principals and Classroom Teachers in optimizing the Minimum Competency Assessment on numeracy. This research used descriptive qualitative research. The research subjects were the principal, grade V teacher, and grade V students. Data collection techniques were passive participation observation, interviews, and questionnaires. The data analysis technique used is Miles and Huberman interactive analysis which consists of data reduction, data presentation, verification, and conclusion drawing. Data validity testing techniques using triangulation techniques. The results of this study are Minimum Competency Assessment has been implemented well with a percentage of 83.1%. Second, students' difficulties in solving problems, namely: difficulties in concepts, difficulties in skills, and difficulties in problem solving. Second, the internal causal factors are attitude and motivation. Lack of variety and learning media, and family environment are external factors. Third, efforts made to reduce the difficulty of solving problems include using concrete learning materials, increasing practice problems, and working with parents.